Association between psychological resilience, social support and oral health behaviours in patients with implant dentures - Tingting Cui; Liying Qiu; Deqiang Hou (BMC Oral Health)
Abstract Background With the improvement of living standards, implant dentures have become the choice of more and more patients with missing teeth. Dentures are not natural teeth, and may cause different degrees of negative impacts on patients in physiological, psychological and social aspects. The objective of this study was to examine the current status of psychological resilience among implant denture patients and the factors that influence it. Additionally, we aimed to analyse the correlation between psychological resilience, social support, and oral health behaviours, with a view to providing a scientific basis for the development of targeted interventions for patients with implant dentures. Methods A survey of 238 patients with implant dentures was conducted in the Department of Stomatology of the Affiliated Hospital of Jiangnan University and Wuxi Stomatological Hospital. The survey included a self-designed general information questionnaire, disease condition questionnaire, The Connor-Davidson Resilience Scale (CD-RISC), The Social Support Rating Scale (SSRS), and The oral health behavior scale. Results The CD-RISC score of patients with implant dentures was 66.49 ± 15.59, while the SSRS score was 37.90 ± 7.73, and the oral health behaviour score was 34.73 ± 7.92. Multiple linear regression analysis showed that age, economic status, social support, and oral health behavioural status were factors influencing the psychological resilience of patients with implant dentures (all P < 0.05), and the psychological resilience score was positively correlated with the score of oral health behaviours and the score of social support (P < 0.05), and the score of oral health behaviours was positively correlated with the score of social support (P < 0.05). Oral health behaviour partially mediated the relationship between psychological resilience and social support. Conclusions The postoperative psychological resilience of patients with implant dentures is at an average level and is affected by various factors, among which social support not only has a direct effect on the psychological resilience of patients with implant dentures, but also has an indirect effect on their psychological resilience through oral health behaviours. Healthcare professionals should actively adopt targeted nursing interventions to improve the psychological resilience of patients, improve their postoperative oral health behaviours, and improve their quality of life. Clinical trial number Not applicable.